2016
DOI: 10.1007/s13205-016-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of pectinases for recovery of grape seeds phenolics

Abstract: Grape marc seeds contain large amounts of different polyphenolic compounds so they can be used for the recovery of these classes of compounds. A new green extraction method for the recovery of phenols from the grape seeds was developed. To provide a high quality extract sourced from natural product by using enzymes as alternative solvents and spending less energy, it is impeccable to call this method “green”. Furthermore, this method was optimized by finding out which conditions provide the best possible resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Three enzymes, such as pectinase, cellulase and tannase, were used to collect and characterize proanthocyanidins located in both the skins and seeds of grape berries, demonstrating that the addition of these enzymes to the extraction mixture increased the total content of phenols [69]. A higher recovery of polyphenols from grape seeds was achieved by the optimization of oenological enzyme preparations composed by cellulases and pectinases [70]. More recently, it was reported that in grape pomace, tannase enriches the phenolic extract in gallic and syringic acids while cellulase enriches it in p-coumaric acid and malvidin-3-O-glucoside [71].…”
Section: Enzymatic Treatments Of Fruit/vegetable Byproductsmentioning
confidence: 99%
“…Three enzymes, such as pectinase, cellulase and tannase, were used to collect and characterize proanthocyanidins located in both the skins and seeds of grape berries, demonstrating that the addition of these enzymes to the extraction mixture increased the total content of phenols [69]. A higher recovery of polyphenols from grape seeds was achieved by the optimization of oenological enzyme preparations composed by cellulases and pectinases [70]. More recently, it was reported that in grape pomace, tannase enriches the phenolic extract in gallic and syringic acids while cellulase enriches it in p-coumaric acid and malvidin-3-O-glucoside [71].…”
Section: Enzymatic Treatments Of Fruit/vegetable Byproductsmentioning
confidence: 99%
“…Pre-extraction of pomace with hot water further increased yields of phenolic compounds [ 74 ]. A recent extraction method for recovery of phenols from grape seed was developed by Stambuk et al [ 75 ] by application of pectinase, an example of enzyme-assisted extraction.…”
Section: Green and Sustainable Procedures: Extraction Techniques mentioning
confidence: 99%
“…The endoglucanases act on the inner region of the cellulose microfibrils (Figure 7B) by releasing oligosaccharides, the exoglucanases act on the cellulose fiber ends releasing units of glucose or cellobiose (formed by two units of glucose), and, finally, beta-glucosidases act on cellobiose releasing glucose units [152]; (ii) Endoproteases (trypsin and chymotrypsin) that degrade proteins that bind phenolics [151]; (iii) Tannase, which catalyzes the hydrolysis of tannins in gallic acid and glucose [152]; and (iv) Glucoamylases that take action under non-reducing ends of starch molecules, generating units of β-D-glucose [153,154]. Other enzymatic preparations, that were studied by some authors in grape/wine by-products, are referred to in Table 1 [155][156][157][158]. In Table 1 we also summarize some works using supercritical fluid extraction (SFE), pressurized liquid extraction (PLE), natural eutectic solvents (NADESs), and enzyme-assisted extraction (EAE) techniques in grape and grape/wine by-products aiming at extraction compounds from grape/wine by-products, that can be used as functional ingredients in the food, nutraceutical, pharmaceutical or cosmetic industries.…”
Section: Enzyme-assisted Extraction (Eae)mentioning
confidence: 99%
“…However, if there is the interest of conduct the work at the industrial level, then we can choose between Supercritical Fluid Extraction (SFE) and Pressurized Liquid Extraction (PLE) [162][163][164][165][166][167][168][169][170][171][172]; or even greener technologies such as the use of ionic liquid (ILs) solvents, deep eutectic solvents (DESs), and natural eutectic solvents (NADESs) [173][174][175][176][177][178]. Enzyme-assisted extraction (EAE) [155][156][157][158] has also been used, even in the winemaking process [179]. The extraction efficiency is dependent on the method used and the material.…”
Section: Grape Seedsmentioning
confidence: 99%